Biomechanical Stability of Femoral Neck System for Pauwels Type III Femoral Neck Fractures Based on Different Reduction Quality - Huang, Daoqiang; Wang, Xiaoping; Chen, Bingze; Hu, Zhiqiang; Feng, Weili (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
To further investigate the biomechanics of a femoral neck system (FNS) for Pauwels type III femoral fractures based on three different reductions.We constructed three different reduction (anatomical reduction, negative buttress reduction, and positive buttress reduction) models of Pauwels type III femoral neck fractures. Then, three cannulated screws (3CS), dynamic hip screws (DHS), dynamic hip screws combined with an anti-rotation screw (DHS + ARS), one-hole femoral neck system (1HFNS), and two-hole femoral neck system (2HFNS) were assembled with the reduction models, respectively, to simulate the internal fixation surgical procedure. All models had a load of 2100 N in line with the femoral mechanical axis applied. The implant stress, the head and implant displacements, and the rotational angles of all models were recorded and analyzed.Compared to 3CS and 2HFNS, 1HFNS had higher implant stress (higher than 92.5 MPa and 46.3 MPa, respectively) and displacement (higher than 0.9 mm and 0.8 mm, respectively) in the anatomical reduction. 2HFNS exhibited the highest stress values (225.5 MPa) in the anatomical reduction but the lowest values (159.8 MPa) in the positive buttress reduction when compared to the other implants. 2HFNS showed the best rotational stability in the negative and positive buttress reduction (rotational angels of 0.8° and 0.6°, respectively).Based on the outcome of this computational study, it might be concluded that 2HFNS was an alternative fixation for the treatment of Pauwels type III femoral neck fracture, especially when anatomical reduction cannot be perfectly attained. More relevant clinical and biomechanical studies are needed in the future.
Keywords: femoral neck fractures; femoral neck system; finite element analysis; reduction quality; biomechanics